Development of Occupational Health Services in Health Centers for Informal Workers - ศักดิ์ชัยนานนท์, บุญเลิศ; จิรนิรัติศัย, โสภาพรรณ (Disease Control Journal, 2011)
The informal workers accounted for 60% of working population in Thailand. However, they often worked in substandard conditions and were exposed to various work hazards in workplaces without health insurance offered by employers or social security. The aim of this quality and quantity study was to develop a model of basic occupational health services in health centers for informal workers in 2008-2009. A sampling was carried out to select health care officers working with 12 groups of informal workers in 4 areas of Muang and Potharam districts, Ratchaburi province. The steps involving in model development of basic occupational health service included participatory action research technique, workshop and training in occupational health services, in-depth interviewing and walk through survey. Data were analyzed using qualitative and quantitative analyses. The results showed that health officers in the study could provide different levels of occupational health services in their health centers. The activities of occupational health services included general health examination and screening for occupational diseases such as finger tip blood screening for pesticide poisoning, primary medical treatment, health education and surveys. In addition, such health services also included collection of health and other relevant information in a family folder, assessment occupational hazards and risk behaviors, provision of proper health education and personal protective equipments. Occupational health volunteers were developed in order to provide occupation health education to the wokers and to coordinate between wokers and health officers. The results of this study could be used as a guideline for setting basic occupational health services in health centers, in particular those that would be further upgraded to be health promoting hospitals. Furthermore the development of occupation health service provision could be considered by policy makers and relevant agencies to be available at all levels of health services and all worker sectors.